2009
DOI: 10.1086/648087
|View full text |Cite
|
Sign up to set email alerts
|

Should Vascular Surgery Patients Be Screened Preoperatively for Methicillin-Resistant Staphylococcus aureus?

Abstract: BACKGROUND Methicillin-resistant Staphylococcus aureus (MRSA) can cause severe infection in patients who are undergoing vascular surgical operations. Testing all vascular surgery patients preoperatively for MRSA and attempting to decolonize those who have positive results may be a strategy to prevent MRSA infection. The economic value of such a strategy has not yet been determined. METHODS We developed a decision-analytic computer simulation model to determine the economic value of using such a strategy befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
17
0
1
Order By: Relevance
“…However, this model was based on data from a hospital in Geneva, which may have lower rates of MRSA colonization than U.S. hospitals. Conversely, using data inputs from the United States, multiple studies found that MRSA screening and decolonization prior to cardiac, vascular, or orthopedic surgery or heartlung transplant was cost-effective from the third-party payer perspective and the hospital perspective (50,(157)(158)(159)(160)(161). However, Lee et al, found that screening and decolonization of pregnant women prior to cesarean delivery were not cost-effective (162).…”
Section: Economic Viabilitymentioning
confidence: 99%
“…However, this model was based on data from a hospital in Geneva, which may have lower rates of MRSA colonization than U.S. hospitals. Conversely, using data inputs from the United States, multiple studies found that MRSA screening and decolonization prior to cardiac, vascular, or orthopedic surgery or heartlung transplant was cost-effective from the third-party payer perspective and the hospital perspective (50,(157)(158)(159)(160)(161). However, Lee et al, found that screening and decolonization of pregnant women prior to cesarean delivery were not cost-effective (162).…”
Section: Economic Viabilitymentioning
confidence: 99%
“…In a mathematical model of the economic benefits of universal screening and decolonisation prior to vascular surgery, universal screening and decolonisation was effective at a prevalence of ≥1% and a decolonisation success rate of ≥50% [20]. Murthy et al [21] compared the costs and probability of occurrence of MRSA infection using (i) PCR screening, (ii) screening for risk factors and pre-emptive isolation and contact precautions pending chromogenic agar results and (iii) no screening in a decision analysis model.…”
Section: Active Screening Of Mrsa Carriers: Universal or Targeted?mentioning
confidence: 99%
“…18,62 Although the vascular and orthopedic surgery populations are similar in many ways (eg, patients tend to be older, with a median age in the mid-60s, and have comorbid conditions; and many procedures are scheduled electively rather than emergently), there are important differences. 18 As may be expected, vascular insufficiency, which can predispose patients to develop postoperative infections, is more common among vascular surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 As before, this model was used to compare 2 decision alternatives: the performance (by means of collecting a swab sample either from the anterior nares or from 2 body sites) or nonperformance of MRSA surveillance (this time, for an orthopedic surgery patient preparing to undergo a surgical procedure). The patient had a probability of being colonized with MRSA that was dependent on the local prevalence of MRSA and individual risk factors for colonization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation